Evolution of desalination research and water production in the Middle East: a five-decade perspective - D’Agostino, Daniele; Al-Memari, Maryam; Burt, John A. (Frontiers in Water, 2025)
IntroductionRapid urbanization and groundwater depletion have entrenched reliance on desalination across the arid Middle East, which now accounts for 46% of global capacity. Yet, the extent to which the region’s research enterprise aligns with rapidly expanding industrial capacity has not been assessed comprehensively.MethodsWe conducted a PRISMA-based systematic review of SCOPUS records to 31 December 2022, identifying 1,899 publications (1972–2022). Scientometric analysis quantified temporal trends in publications, research themes, authorship geography and technological advancements. Desalination plant data (1950–2027) from Global Water Intelligence were used to derive national capacities. Associations between research, capacity and socio-economic or water-stress metrics were tested with correlation and linear models.ResultsPublications rose sharply after the early 2000s, with 83% published between 2013 and 2022. Dominant themes were energy efficiency (24%) and institutional/regulatory concerns (22%), followed by treatment improvements and cost–benefit analyses ( 11% each). Authorship was primarily region-based ( 80%), a stark contrast with other research fields. In 2022, regional capacity reached 45 million m³ d-1 (Saudi Arabia 17; UAE 11), with 60 million projected by 2027. GDP correlated strongly with publication volume (r = 0.90) and capacity (r = 0.83); publications and capacity were also correlated (r = 0.74), while population and water-stress metrics were not. Research focus shifted from thermal to membrane technologies, yet 50% of regional capacity remains thermal versus >95% non-thermal globally.ConclusionsThese findings underscore the central role of desalination research and water production in regional water security and highlight the need to better align research priorities with operational realities and environmental safeguards through targeted innovation and cross-sector collaboration.